Midostaurin Reverses ABCB1-Mediated Multidrug Resistance, an in vitro Study - Ji, Ning; Yang, Yuqi; Cai, Chao-Yun; Wang, Jing-Quan; Lei, Zi-Ning; Wu, Zhuo-Xun; Cui, Qingbin; Yang, Dong-Hua; Chen, Zhe-Sheng; Kong, Dexin (Frontiers in Oncology, 2019)
Overexpressing of ABC transporter in cancer cells is involved in the multidrug resistance (MDR), which leads to insensitive response to chemotherapy. In this study, we found midostaurin, a Food and Drug Administration (FDA)-approved anti-leukemia drug, can antagonize ATP-binding cassette subfamily B member 1 (ABCB1)-mediated MDR. Our results showed that midostaurin significantly antagonized ABCB1-mediated MDR, but not the MDR mediated by ATP-binding cassette subfamily G member 2 (ABCG2). Mechanism studies showed that midostaurin reversed MDR by inhibiting the function of the ABCB1 without downregulating or change of subcellular localization of ABCB1 transporter. In addition, midostaurin inhibited the ATPase activity of ABCB1 in a concentration-dependent manner, and the in silico docking study predicted that midostaurin could interact with the substrate-binding sites of ABCB1 transporter. Our finding provides a potential treatment strategy that co-administrating midostaurin with anticancer drugs in clinic may overcome MDR and improve the efficiency of cancer treatment.